Aspectos ecológicos de una comunidad de anuros en un ambiente tropical estacional en Guanajuato, México - Leyte-Manrique, Adrian; González-García, Ruth Liliana E.; Quintero-Díaz, Gustavo Ernesto; Alejo-Iturvide, Francisco; Berriozabal-Islas, Christian (Instituto de Ecología, A.C., 2018)
In this study we compared ecological aspects of the use of the microhabitat and period of activity of an anuran community in four types of vegetation (deciduous tropical forest, gallery forest, xerophilous scrub and induced pasture) in a seasonal tropical environment of the southwestern region of the state of Guanajuato, Las Musas Protected Natural Area. There were nine species of anurans, three toads and six frogs, of which the most abundant was Lithobates neovolcanicus (152 individuals), and the least abundant, with only one individual Craugastor occidentalis and Spea multiplicata. We characterized 17 different types of microhabitats, differences between species (H = 0.22, P = 0.01) exist in terms of their use. The vegetation types with the greatest heterogeneity of microhabitats were the low forest and the gallery forest in comparison with the xerophilous and grassland scrub. Species that used most microhabitats were L. neovolcanicus, Anaxyrus compactilis and Dryophytes eximius. The highest overlap was recorded between A. compactilis and Incilius occidentalis (100%), followed by I. occidentalis and D. arenicolor (89%), and I. occidentalis and L. neovolcanicus (72%). The longest periods of activity were recorded in A. compactilis (10:28 to 22:10 hrs) and L. neovolcanicus (10:40 to 22:20 hrs). A positive relationship was found between the body temperature and temperature of the microhabitat and the environmental one for A. compactilis, I. occidentalis, D. eximius, D. arenicolor and L. neovolcanicus. The community of anurans present in the study area can be differentiated into three eco-structural components, according to their habits; aquatic, saxicolous-terrestrial and arboreal species, determined, both by their habits for the selection of microhabitats, and their daily activity periods. We consider that although plant heterogeneity is important in the distribution of species and availability of microhabitats, it is not the main factor in the selection and use of microhabitats by species as was supposed. But the selection and use of the microhabitats and composition of the community of anurans, is determined by behavioral events that are manifested in the periods of activity and thermoregulatory capacity of each species, as a physiological response to the influence of the temperature.